EXPLORING THE AUTHOR'S INDIVIDUAL WORLD IMAGE: A SCHOLARLY ANALYSIS OF TEXTUAL CONTENT, STYLE, AND PERSPECTIVE IN TRANSLATED WORKS FROM ENGLISH TO UZBEK - Khayrieva Madina Ilhomovna; Muhammedova Mohinur Bakberganovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
With an emphasis on maintaining and understanding each author's unique worldview, this article provides a thorough study of the steps involved and the results of translating literary works from English to Uzbek. This research sheds light on the difficulties translators encounter in capturing the spirit of the source material while navigating language and cultural barriers. It does this by carefully analyzing the text's style, perspective, and subject and providing examples from literature.